2016
DOI: 10.1016/j.epsl.2016.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of remote triggering: A survey of multiple fault structures in Haiti

Abstract: International audienceTriggering studies provide an important tool for understanding the fundamental physics of how faults slip and interact, and they also provide clues about the stress states of faults. In this study, we explore how seismic waves from the 27 February 2010 Mw8.8 Maule, Chile mainshock interact with the left lateral strike-slip Enriquillo–Plantain Garden Fault (EPGF) and surrounding reverse faults in the southern Haiti peninsula. The Chile mainshock occurred 6,000 km away and just 46 days afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…If dynamic triggering preferentially triggers small magnitude quakes, as has been suggested in previous studies 20,34,47 , further enhancement of these regional catalogs may lead to more instances of potential dynamic triggering. However, the Mc levels for the regional earthquake catalogs used in this study are already relatively low (all time periods <2.5; majority of time periods <1.5; Supplementary Fig.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…If dynamic triggering preferentially triggers small magnitude quakes, as has been suggested in previous studies 20,34,47 , further enhancement of these regional catalogs may lead to more instances of potential dynamic triggering. However, the Mc levels for the regional earthquake catalogs used in this study are already relatively low (all time periods <2.5; majority of time periods <1.5; Supplementary Fig.…”
mentioning
confidence: 59%
“…Causality is assumed primarily because local events are either coincident with the passage of the surface waves, as determined by the presence of local earthquakes in the wavefield [11][12][13][14][15] or the triggered events initiate within several hours after the passage of the mainshock seismic waves, leading to the concept of delayed dynamic triggering [16][17][18][19] . The prevalence of identified mainshocks generating remote, small magnitude earthquakes has led to two hypotheses: (1) remote dynamic triggering is ubiquitous 13 and (2) dynamically triggered events are small, often below the magnitude of completeness (Mc) and to identify these events requires catalog enhancement 14,[20][21][22][23][24] .…”
mentioning
confidence: 99%
“…Either hypothesis provides a possible explanation as to why we observed a midcrustal velocity reduction along the PGJF. Some studies mentioned that low‐velocity anomaly sometimes occurred on active fault systems [ Eberhart‐Phillips and Bannister , ; Eberhart‐Phillips and Reyners , ], but in our case study, despite the fact that Aiken et al [] have found light correlation between tremor sources and the low‐velocity anomalies along the PGJF, we do not have enough information to confirm if the PGJF is active or not. Nevertheless, at 10 km depth, this anomaly seems to extend further offshore to the south and to the north.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, tremor has been well studied since its first discovery in the subduction zone beneath southwest Japan [Obara, 2002]. It is now observed along many plate-boundary faults, including subduction zones in Cascadia [Rogers and Dragert, 2003], New Zealand [Kim et al, 2011], Mexico [Payero et al, 2008], Alaska [Peterson and Christensen, 2009], Costa Rica [Walter et al, 2011] and Southern Chile [Gallego et al, 2013], as well as strike-slip faults and other inland faults in Central California [Nadeau and Dolenc, 2005], Haida Gwaii , Cuba , Haiti [Aiken et al, 2016], and Indonesia [Fuchs et al, 2014;Bansal et al, 2016]. Tremor can either occur spontaneously, or be triggered by large teleseismic earthquakes [Rubinstein et al, 2007;Gomberg et al, 2008;Peng and Chao, 2008;Peng et al, 2009;Chao et al, 2012aChao et al, , 2012b, regional earthquakes [Guilhem et al, 2010], or tides Nakata et al, 2008;Thomas et al, 2009].…”
Section: Introductionmentioning
confidence: 99%